School nurse asthma program reduces healthcare utilization in children with persistent asthma. (3rd October 2018) - Trivedi, Michelle; Patel, Janki; Lessard, Darleen; Kremer, Ted; Byatt, Nancy; Phipatanakul, Wanda; Pbert, Lori; Goldberg, Robert
ABSTRACT: Objective : We examined the impact of a novel, school nurse-supervised asthma therapy program on healthcare utilization. Methods : We retrospectively reviewed charts of 84 children enrolled in this program in central Massachusetts between 2012 and 2015. Physicians identified children with persistent asthma and poor medication adherence. These children were enrolled in the program to receive daily-inhaled corticosteroid at school, supervised by their school nurse, with ongoing communication between physician's office and school nurse through the school year. This program relied on established family, provider and school resources rather than research staff. The primary outcome was change in the number of emergency department (ED) visits in the year before and after enrollment. Secondary outcomes were hospital admissions, school absences, and rescue medication use. Results : The study population was on average 10.5 years old, 63% male, 67% Hispanic, 19% black, 14% white with 95% using Medicaid insurance. Asthma-related ED visits over a 1-year period decreased 37.5%, from a pre-intervention mean of 0.8 visits to a post-intervention mean of 0.3 visits ( p < 0.001). Asthma-related hospital admissions decreased from a pre-intervention mean of 0.3 admissions to post-intervention mean of 0 admissions ( p < 0.001). Asthma rescue medication refills decreased by 46.3% from the pre- to post-intervention period ( p = <.001). There were also non-significant declines in school absences and oral steroid use for children enrolled. Conclusions : We demonstrate a significant reduction in healthcare utilization for children enrolled in this unique school nurse-supervised asthma program, which utilizes a clinical-school partnership to deliver preventative asthma medication to school-aged children under sustainable conditions.